Analysis Dynamics of Adolescents' Lack of Openness to Parents: A Qualitative Study - Maulina, Yesika; Fitriani, Wahidah; Yeni, Putri; Maharjan, Kailie (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Communication between adolescents and parents plays an important role in the emotional development and mental health of adolescents. The method used in this study is a literature review, by analyzing various studies related to family communication and adolescents' lack of openness. The results of the study indicate that lack of openness in communication can increase anxiety, stress, depression, and feelings of isolation in adolescents. In addition, lack of openness can also affect academic achievement and social behavior in adolescents. Some factors that influence this lack of openness include parenting style, family dynamics, adolescents' personal experiences, and cultural norms. This study also highlights the importance of open communication in the family, where parents who listen to and support adolescents' emotions can help reduce anxiety and improve their emotional health. In the context of Indonesian culture, social norms that value parental authority often cause adolescents to be reluctant to speak openly. These findings are expected to provide insights to improve family communication and support adolescents' emotional well-being through a more open and empathetic approach.